1989
DOI: 10.1121/1.2026927
|View full text |Cite
|
Sign up to set email alerts
|

Scattered ambient noise as an auditory stimulus for fish

Abstract: In an earlier paper [P. H. Rogers, J. Acoust. Soc. Am. Suppl. 1 79, S22 (1986)], it was hypothesized that one role of the fish's auditory system may be to detect and localize nearby fish by “imaging” ambient noise scattered by their swim bladders. This is analogous to the role of the visual system of most animals, where the relevant signal is ambient light scattered by objects rather than light emitted by luminous objects. A classical conditioning experiment has been performed which indicates that the fish aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The answer to the question, 'What do fish listen to?' is 'all sounds', including what is termed 'ambient noise' [Rogers, 1986;Rogers et al, 1989;Lewis and Rogers, 1992].…”
Section: To What Do Fish Listen?mentioning
confidence: 99%
“…The answer to the question, 'What do fish listen to?' is 'all sounds', including what is termed 'ambient noise' [Rogers, 1986;Rogers et al, 1989;Lewis and Rogers, 1992].…”
Section: To What Do Fish Listen?mentioning
confidence: 99%
“…A preliminary study showed goldfish could detect simulated scattered ambient noise in an ambient noise masker (Rogers et al, 1989). In this study, two goldfish (about 15 an in length) were classically conditioned to suppress their heart rate upon presentation of an acoustic stimulus simulating the scattered noise.…”
Section: -45mentioning
confidence: 97%
“…A second preliminary experiment, shown in Figure 7, was conducted to show that goldfish could detect simulated scattered ambient noise in a noise masker (Rogers et al, 1989). In this experiment, threshold of the scattered noise as a function of distance from the fish was determined using classical heart rate conditioning.…”
Section: Response To Scattered Ambient Noisementioning
confidence: 99%